Influence of non-genetic factors on first lactation and lifetime performance traits in Nili-Ravi buffaloes - Tamboli, Pooja; Bharadwaj, Anurag; Chaurasiya, Amit Kumar; Jan, Mustafa H.; Kumar, Sanjay; Khanna, Sudhir (Frontiers in Animal Science, 2023)
The livestock data on first lactation and lifetime performance traits relevant to 501 Nili-Ravi buffaloes was collected from the history sheet of animal for a period from 1983 to 2017 (35 year) maintained at ICAR-CIRB sub-campus, Nabha, Punjab. The overall least-square means for age at first calving (AFC) was 45.03±0.40 months. The results indicated that the effect of age at first calving was highly significant (p≤0.01) on first lactation total milk yield (FLTMY), first lactation standard milk yield (305 days or less) (FLSMY), first peak milk yield (FPY) and first lactation length (FLL) in the Nili-Ravi breed of buffaloes. The FLTMY, FLSMY and FPY were highest (2250.08±48.16 kg, 1944.68±31.20 kg and 9.32±0.16 kg/day) for the animals having AFC of 42-48 months. Furthermore, the FLTMY, FLSMY and FLL was highest (2411.02±68.68 kg, 2008.81±44.49 kg and 357.43±8.13 days) in the animals first calved in autumn season. However, lowest FDP, FSP and FCI (110.63±7.42 125.48±9.04 and 443.63±9.00 days) were found for the animals first calved in rainy season. The overall least-square means for herd life (HL), productive life (PL), productive days (PD), unproductive days (UD), total lifetime milk yield (Total LTMY), standard lifetime milk yield (Standard LTMY), milk yield per day of productive life (MY/PL), milk yield per day of productive days (MY/PD) and milk yield per day of herd life (MY/HL) were estimated as 3779.84±31.86 days, 2078.55±24.32 days, 1552.74±20.06 days, 525.81±12.44 days, 10229.71±195.31 kg, 9203.64±173.52 kg, 4.86±0.08 kg/day, 6.46±0.08 kg/day and 2.66±0.04 kg/day. The effect of age at first calving was highly significant (p≤0.01) on HL, PD, UD, Total LTMY and Standard LTMY. Further, the effect of season of first calving was significant (p≤0.05) on HL, PL and PD. Additionally, the effect of period of first calving was significant (p≤0.05) on HL, PD, Standard LTMY and Total LTMY. In these contexts, it can be concluded that the animals in the Nili-Ravi breed having age at first calving from 42-48 months performed better in terms of production, reproduction and lifetime traits.